Türkiye'de yerel yönetimlerin konut üretimindeki yeri: Malatya ve Elazığ örneği - Polat, Yeliz; Yatkın, Ahmet (My University, 2016)
Cumhuriyetin ilk yıllarından günümüze siyasal kara vericiler uygulamaya koydukları pek çok yasal düzenleme ve politikayla, kamunun hem merkezi hem de yerel örgütlenmeler ölçeğinde konut üretimini gerçekleştirmesini sağlamıştır. Ancak tüm bu çabalara karşın konut talepleri istenilen düzeyde karşılanamamıştır ve konut üretiminde baskın bir biçimde özel sektör kamunun önünde yer almıştır. Bu araştırma kapsamında özel sektörün konut temininde neden bu denli baskın olduğunu tartışmak yerine, yerelleşme politikaları çerçevesinde belediyelerin konut üretiminde üstlendikleri, daha da önemlisi üstlenebilecekleri rol araştırma konusu yapılmıştır. Bu araştırmada, Malatya ve Elazığ Belediyelerince hayata geçirilen konut üretim örnekleri çözümlenerek Türkiye’de yerel yönetimlerin konut üretimindeki yeri ortaya konulmuştur.

Dating from the very first years of the Turkish Republic until today, political authorities, with the help of legal regulations and policies that were put into parctice, have governments the public to realize the dwelling production within the scale of central and local organizations. Nevertheless, despite all these struggles, the demand for dwelling has never been covered up to the mark and private sector has been one step ahead of public initiatives preponderantly. Within the scope of this sudy, instead of discussing why the private initiatives have been so dominant at dwelling supply, the part that municipalities have taken in dwelling production until now, and more importantly the role that they may play in the future has been the subject of this research within the frame of indigenisation. In this research, after analyzing the dwelling production examples that were come to realize by the municipalities of Malatya and Elazığ, the point that local governments in Turkey may reach has been made clear.
The role of local governments in dwelling production in Turkey: The instances of Malatya and Elazığ
Bildiri - Yayımlanmış
Keywords: Konut; Yerel yönetimler; Belediyeler; Belediye İktisadi Teşekkülleri; Local governments; Municipality; Municipality Economic Enterprises; Dwelling